Transformation of Educational Management in Shaping the Character of Santri at the Purba Baru Musthafawiyah Traditional Islamic Boarding School - Sabli, Muhammad; Ritonga, Ahmad Husein; Shalahudin, Shalahudin (Journal of Social Work and Science Education, 2023)
The purpose of this study is to determine the impact of educational management on the character development of students at the Musthafawiyah Purba Baru Traditional Islamic Boarding School in Mandailing Natal Regency, North Sumatra Province. This is a descriptive qualitative study in which data was gathered through observation, interviews, and documentation. The research subjects included foundation administrators, pesantren leaders and vice-chairmen, teachers, and students. According to the findings of the study, the transformation process of educational management in forming the character of students at the Musthafawiyah Purba Baru Traditional Islamic Boarding School, Mandailing Natal Regency, North Sumatra Province, has been implemented in the form of a clean, honest, disciplined, trustworthy, independent, respectful, and simple character carried out through yellow book learning activities. Kyai, teachers, hostel supervisors, peers, and yourself all internalize these character values. Despite the fact that it is not optimally responsive to the times and has yet to determine the focus of character development.